Unisphere and fountains
Caption, "From the New York World's Fair, Unisphere - The Unisphere, theme symbol of the New York World's Fair 1964-1965 is a marvel of modern steel design, fabrication and construction. Built and presented to the Fair by United States Steel Corp., it is the largest representation of the planet Earth ever constructed and symbolizes the theme of the Fair, "Peace through Understanding." The fourteen storey tall structure, weighing 380 tons and resting on a 70 ton base, is encircled at its base by the 310 foot reflective Fountain of the Continents and is girded by three stainless steel orbits, each weighing three tons and representing the path of a man-made satellite orbiting the earth. These are held in place the same way the rim of a bicycle wheel is attached to its hub, by high strength stainless steel strands of "spokes." These factors give the structure the appearance of being graceful, yet grand, light yet massive, solid yet transparent."